IMPLEMENTASI PRINSIP SWAKRAMAWI DALAM KITAB ETIKA PARIWARA INDONESIA SEBAGAI STRATEGI PENGUATAN ETIKA PROFESI PERIKLANAN NASIONAL - Doni Abdullah Alhafidz; Akrom Maulana; Said Khalid; Noval Prasetya; Daniel Handoko (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The Indonesian Advertising Ethics Code (EPI) serves as a fundamental ethical foundation and behavioral guideline for practitioners in the national advertising industry. One of its core principles is swakramawi or self-regulation, a form of ethical governance rooted in the awareness and voluntary adherence of industry players. This study aims to analyze the implementation of the swakramawi principle in the 2020 amendment of EPI and its role in strengthening the ethics of the advertising profession in Indonesia. The research employs a descriptive-qualitative literature study based on academic references from the past five years. The findings reveal that swakramawi not only forms the basis of internal norms but also acts as a strategy to build advertising practices that are responsible, honest, and culturally contextual. This study highlights the importance of integrating internal ethics through EPI as a dynamic instrument capable of addressing the challenges of digital advertising and media disruption. The results provide a reference for both practitioners and academics in enhancing the synergy between industry regulations and moral values in marketing communication professions in Indonesia.